Trajectory Tracking Control of Pneumatic Cylinder-Actuated Lower Limb Robot for a Gait Training System - Tran, Van-Thuc; Nguyen, Ba-Son; Vu, Tiendung; Bui, Ngoc-Tam (Engineering, Technology & Applied Science Research, 2024)
This article presents the design of a control strategy for a lower limb gait training system catering to patients with Spinal Cord Injury (SCI) or stroke. The system operates by driving the hip and knee joints individually through pneumatic cylinders. The focus lies on the study and development of a control strategy for the pneumatic actuators within the gait training system, specifically targeting trajectory tracking control of pneumatic double-acting cylinders utilizing a PID Controller. The experiment setup comprises a pneumatic cylinder regulated by a proportional valve, incorporating feedback via position and pressure sensors. The experimental results show that the system exhibits good trajectory-tracking performance, particularly at low frequencies.